Development of Real-Time Quantitative Polymerase Chain Reaction Assays to Track Treatment Response in Retinoid Resistant Acute Promyelocytic Leukemia - Jovanovic, Jelena V.; Rennie, Kristian; Culligan, Dominic; Peniket, Andrew; Lennard, Anne; Harrison, Justin; Vyas, Paresh; Grimwade, David (Frontiers in Oncology, 2011)
Molecular detection of minimal residual disease (MRD) has become established to assess remission status and guide therapy in patients with PML-RARA+ acute promyelocytic leukemia (APL). However, there are few data on tracking disease response in patients with rarer retinoid resistant subtypes of APL, characterized by PLZF-RARA and STAT5b-RARA. Despite their relative rarity (<1% of APL) we identified 6 cases (PLZF-RARA, n=5; STAT5b-RARA, n=1), established the respective breakpoint junction regions and designed real-time quantitative polymerase chain reaction (RQ-PCR) assays to detect leukemic transcripts. The relative level of fusion gene expression in diagnostic samples was comparable to that observed in t(15;17)-associated APL, affording assay sensitivities of ~1 in 104-105. Serial samples were available from 2 PLZF-RARA APL patients. One showed persistent PCR positivity, predicting subsequent relapse, and remains in CR2, ~11 years post-autograft. The other, achieved molecular remission (CRm) with combination chemotherapy, remaining in CR1 at 6 years. The STAT5b-RARA patient failed to achieve CRm following frontline combination chemotherapy and ultimately proceeded to allogeneic transplant on the basis of a steadily rising fusion transcript level. These data highlight the potential of RQ-PCR detection of MRD to facilitate development of more individualized approaches to the management of rarer molecularly-defined subsets of acute leukemia.